2013
DOI: 10.3762/bjoc.9.41
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted three-component domino reaction: Synthesis of indolodiazepinotriazoles

Abstract: SummaryA microwave-assisted three-component protocol involving N-1 alkylation of 2-alkynylindoles with epichlorohydrin, ring opening of the epoxide with sodium azide, and an intramolecular Huisgen azide–internal alkyne 1,3-dipolar cycloaddition domino sequence has been described. The efficacy of the methodology has been demonstrated by treating various 2-alkynylindoles (aromatic/aliphatic) with epichlorohydrin and sodium azide furnishing annulated tetracyclic indolodiazepinotriazoles in satisfactory yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Starting materials 1a – h were prepared according to the literature procedure . The characterization data of compounds 1a – f and 1h were reported previously by us …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting materials 1a – h were prepared according to the literature procedure . The characterization data of compounds 1a – f and 1h were reported previously by us …”
Section: Methodsmentioning
confidence: 99%
“…In a continuation of our efforts on the one-pot synthesis of diverse heterocycles from 2-alkynyl indoles, which acts as a combined source for both a nucleophile (indole) and an electrophile (an internal alkyne), we embarked on yet another application involving the construction of 2,4 -substituted NH-carbazoles by treating the 2-alkynyl indole with a terminal aryl alkyne. We envisioned that initially the terminal alkyne may undergo hydroarylation with 2-alkynyl indole via metal-catalyzed activation to form an enyne intermediate, which may then undergo intramolecular carbocyclization to afford NH-carbazoles.…”
mentioning
confidence: 99%
“…Recently, Arigela et al (2013) reported a microwave-assisted three component domino synthesis of indolodiazepinotriazoles involving N-1 alkylation of 2-alkynylindoles with epichlorohydrin, ring opening of the epoxide with sodium azide and intramolecular Huisgen azide/internal alkyne 1,3-dipolar cycloaddition domino sequence. Various 2-alkyl indoles (aromatic/aliphatic) with epichlorohydrin and sodium azide have been used affording annulated tetracyclic indolodiazepinotriazoles with satisfactory yields.…”
Section: 3-dipolar Additionmentioning
confidence: 99%